Non-Preferential Clubs - Pascalis Raimondos-Møller; Alan D. Woodland (University of Copenhagen, Economic Policy Research Unit (EPRU), 2002)
This paper examines the welfare implications of non-discriminatory tariff reforms by a subset of countries, which we term a non-preferential trading club. We show that there exist coordinated tariff reforms, accompanied by appropriate income transfers between these countries, that unambiguously increase the welfare of these member countries while leaving the welfare of non-members unaltered. These tariff reforms are chosen to maintain world prices at their pre-club levels and, in this respect, the trading clubs act in a Kemp-Wan-like manner. In terms of economic policy implications, our results show that there exist regional, MFN-consistent arrangements that lead to Pareto improvements in world welfare. Open regionalism is an example of such trading arrangements.
Keywords: 330; Handelspräferenzen; Zollunion; Theorie